Prevalence in the Italian regions of pain in patients with diabetic peripheral neuropathy (NDP) and the current costs of drug treatment for principals with specific indication - Guidi, Luca (Farmeconomia. Health economics and therapeutic pathways, 2010)
The present analysis estimates the prevalence of pain in patients affected by peripheral diabetic neuropathy referring to Italian and English data published recently and the cost of pharmacological treatments related to specifically indicated drugs. 16% of diabetic patients in Italy is affected by pain symptoms during PDN (peripheral diabetic neuropathy). The corresponding prevalence is 425,168 cases annually. A little number of these patients is actually treated with specifically indicated drugs (duloxetine, pregabalin and gabapentin), anyway the increase of share of duloxetine treatments would take to significant savings due to its lower costs among the specifically indicated pharmacological options.